(3GddjK GdYGHS aj UOeGJ GdeLGdSs - (3ESeGYjd Hf Ydj Hf MSf GdUYjOj GdbGgQj GdTGaYj, GHf eYdjs ((3Ce GdNjQ HfJ HQgGf GdOjf s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ GSeGYjd Hf eYdi s
(3BNQgG (B:s
(3hcKQI GdJHY eGdGjONd hSYg hGdceGd ddg YR hdcJGHg GdYRjR s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B370s
Keywords: (3CUhd Gdabgs